2019
DOI: 10.1038/s41598-019-47855-5
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the trigeminovagal complex in the human medulla by combining ex-vivo ultra-high resolution structural MRI and polarized light imaging microscopy

Abstract: A trigeminovagal complex, as described in some animals, could help to explain the effect of vagus nerve stimulation as a treatment for headache disorders. However, the existence of a trigeminovagal complex in humans remains unclear. This study, therefore investigated the existence of the trigeminovagal complex in humans. One post-mortem human brainstem was scanned at 11.7T to obtain structural (T1-weighted) and diffusion magnetic resonance images ((d)MR images). Post-processing of dMRI data provided track dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
(64 reference statements)
3
18
0
Order By: Relevance
“…SpV activation in response to RAVANS is consistent with previous findings from our group [26]. SpV is the main nucleus for trigeminal sensory afference from the head, and a recent study suggested the existence of a "trigeminovagal complex" in the human medulla, where afferent vagus and trigeminal systems connect anatomically [50]. More surprisingly, our response cluster possibly extends to the dorsal column nuclei, namely gracilis and cuneatus, known to relay touch and proprioceptive afference from the lower and upper body, respectively [46].…”
Section: Discussionsupporting
confidence: 91%
“…SpV activation in response to RAVANS is consistent with previous findings from our group [26]. SpV is the main nucleus for trigeminal sensory afference from the head, and a recent study suggested the existence of a "trigeminovagal complex" in the human medulla, where afferent vagus and trigeminal systems connect anatomically [50]. More surprisingly, our response cluster possibly extends to the dorsal column nuclei, namely gracilis and cuneatus, known to relay touch and proprioceptive afference from the lower and upper body, respectively [46].…”
Section: Discussionsupporting
confidence: 91%
“…nVNS has also been reported to inhibit the nitroglycerin-mediated increase in glutamate levels in cerebral spinal fluid in a model of trigeminal allodynia (24). Another possible mechanism of nVNS involves the direct regulation of pain signaling in the upper spinal cord based on data from a recent human imaging study that provided evidence of the trigeminal and vagus systems being interconnected at the level of the spinal trigeminal nucleus (43). Taken together, the inhibitory effect of nVNS in migraine is facilitated via multiple mechanisms that function to suppress peripheral and central sensitization of the trigeminal system and inhibit pain signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fiber orientations were encoded by hue, saturation and brightness values. Comparison with other color encoding schemes often used in dMRI studies has been described in previous publications ( Axer et al, 2011b ; Henssen et al, 2019a ; Henssen et al, 2019b ).The reference for a single vector representation is often not a single fiber, but all birefringent tissue compartments inside a volume element (voxel) contribute to the measured signals.…”
Section: Methodsmentioning
confidence: 99%